From Caméra-Stylo to Photobook: On Chris Marker’s Staring Back - Baetens, Jan (Cinémas, 2012)
In this article, the author analyzes Chris Marker’s photography, in particular the project Staring Back (an exhibition and a book, published in 2007), which offers a synthesis in fixed images of the film career of this author who has always explored the blurred boundaries between the still and the moving image (for example in his 1962 cult movie La jetée, or in later photo-films such as Si j’avais quatre dromadaires, 1966, and Le souvenir d’un avenir, with Yannick Bellon, 2001). The author relies on Marker’s notion of the “superluminal” (which refers to a special way of selecting still images out of the flow of moving images) as well as on contemporary and historical discussions on intermediality (inside and outside the domain of film studies alone) and cinephilia (as a specific way of combining writing and filming), to propose a close reading of Staring Back. In this reading, the author places strong emphasis on the political issues around looking and the relationship between artist and model.